Teaching Method in EFL Classroom: Types and Why Techers Use It? - Anggraini, Dwinesa; Dewi, Hernalia Citra (BRIGHT : A Journal of English Language Teaching, Linguistics and Literature, 2025)
Teaching methods are very important in teaching learning process.  It's an essential thing for teachers. To provide students with a good quality of education, it's very possible for teachers to use more than one way to teach in dynamic classroom. The aim of this research is to get to know the various teaching method used by teachers and the reason why they use it. The research method used is a descriptive qualitative method. The data are taken from teachers in "Komunitas Belajar Riset dan Aksi". The researchers use observation, interview, and questionnaire in collecting the data. The data are analyzed using data display, data verification and the last data reduction. The result of this research shows that there are three teaching methods that commonly used; there are small group discussion, brainstorming, and project based learning. In addition, there are some factors why teachers select those teaching methods such as seeing the students' needs, time availability, comfortablity, and flexibility in using it.